2017
DOI: 10.1155/2017/9536458
|View full text |Cite
|
Sign up to set email alerts
|

Dahuang Fuzi Decoction Attenuates Renal Fibrosis and Ameliorates Mitochondrial Dysfunction in Chronic Aristolochic Acid Nephropathy

Abstract: Objectives. The effects of the traditional formula Dahuang Fuzi Decoction (DFD) on chronic aristolochic acid nephropathy (AAN) in mice and its underlying mechanisms were studied. Methods. Mice were randomly divided into the following six groups: the control group, the model group (AAN), the saline-treated group (AAN + vehicle), the normal dose DFD-treated group (AAN + NDFD), the high dose DFD-treated group (AAN + HDFD), and the rosiglitazone treated group (AAN + Rosi). After treating for 8 weeks, 24 h urine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It was also associated with a decrease in ATP, a change in mitochondrial membrane potential and oxygen consumption rate (Zhou et al, 2013). Similar findings were also presented by Shui et al (2017). In addition, some metabolomics/metabonomics studies (Cui et al, 2019; Ni et al, 2007) revealed that aristolochic acid leads to disruption, perturbation and inhibition of amino acid, fatty acid, glucose and purine metabolism, as well as impairment of Krebs cycle and ATP energy supply.…”
Section: Energy Charge Changes In Aristolochic Acid Intoxicationsupporting
confidence: 92%
See 1 more Smart Citation
“…It was also associated with a decrease in ATP, a change in mitochondrial membrane potential and oxygen consumption rate (Zhou et al, 2013). Similar findings were also presented by Shui et al (2017). In addition, some metabolomics/metabonomics studies (Cui et al, 2019; Ni et al, 2007) revealed that aristolochic acid leads to disruption, perturbation and inhibition of amino acid, fatty acid, glucose and purine metabolism, as well as impairment of Krebs cycle and ATP energy supply.…”
Section: Energy Charge Changes In Aristolochic Acid Intoxicationsupporting
confidence: 92%
“…Exactly the described decreased concentration of nucleotides due to the formation of adducts with aristolochic acid could contribute, among other mechanisms, to the cell energy crisis, leading to aristolochic acid nephropathy fibrosis as a consequence of apoptosis/necrosis. Indeed, it has been undoubtedly confirmed that aristolochic acid interferes with cellular energy production (Cui et al, 2019; Jiang et al, 2013; Ni et al, 2007; Qi et al, 2007; Romanov et al, 2011; Shui et al, 2017; Zhou et al, 2013) and the proposed hypothesis of aristolochic acid‐induced ATP depletion by direct covalent interaction with adenosine in ATP, among other molecules, may gain a central role in explaining the aristolochic acid‐induced energy crisis. It provides unique consolidation among the already proven aristolochic acid nephropathy energy crisis mechanisms that are directly or indirectly related to the ATP pool.…”
Section: Aristolochic Acid Adducts and Potential Consequences Of Their Structuresmentioning
confidence: 99%
“…Furthermore, treatment with emodin significantly inhibited inflammation‐related factors and oxidative stress, suppressed the expression of intercellular adhesion molecule 1 (ICAM‐1) and Bax, increased phosphorylated Akt and phosphorylated‐glycogen synthase kinase 3 (p‐GSK‐3β) expression and inhibited Caspase‐3 activity in diabetic rats [37] . In addition, Rhubarb could decrease the serum creatinine (SCr), blood urea nitrogen (BUN) and urine protein (UP) values in vitro and in vivo, which suggested that it displayed certain therapeutic and preventive effects against the diabetic nephropathy [38–41] . Our study indicates that Rhubarb plays an anti‐inflammatory and anti‐apoptosis role in LPS‐induced renal injury by increasing the expression of AMPK and Bcl‐2, and suppressing the NF‐κB, Bax, Caspase‐3, and Cleaved Caspase‐3, strongly suggesting that Rhubarb may be used as a potential drug for the treatment of DKD in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Shui et al 71 found that Dahuang Fuzi Decoction could attenuate renal brosis and ameliorates mitochondrial dysfunction in chronic aristolochic acid nephropathy. Besides, Dahuang Fuzi Decoction could alleviate adenine-induced tubular epithelial apoptosis and renal damage in vivo, presumably through the suppression of TGF-β1-JNK pathway activation 72 .…”
Section: Delaying Renal Brosismentioning
confidence: 99%